Effect of hierarchical meso–macroporous structures on the catalytic performance of silica supported cobalt catalysts for Fischer–Tropsch synthesis. Issue 17 (9th August 2017) - Li, Hansheng; Hou, Bo; Wang, Jungang; Huang, Xin; Chen, Congbiao; Ma, Zhongyi; Cui, Jinglei; Jia, Litao; Sun, Dekui; Li, Debao
Abstract : A series of meso–macroporous silica supports with the same macroporous diameter but different mesoporous diameters were prepared by introducing phase separation into a sol–gel process and used to prepare cobalt catalysts for Fischer–Tropsch synthesis. Abstract : A series of meso–macroporous silica supports with the same macroporous diameter but different mesoporous diameters were prepared by introducing phase separation into a sol–gel process and used to prepare cobalt catalysts for Fischer–Tropsch synthesis. The mesoporous diameter could be controlled in the range 6.5–35.0 nm while the macroporous diameter was kept at approximately 500 nm. The mesoporous porosity of the meso–macroporous silica supports greatly influenced the size, reducibility and dispersion of cobalt nanoparticles, and therefore resulted in different catalytic performances for Fischer–Tropsch synthesis. The meso–macroporous catalyst with an appropriate mesoporous size of 8.5 nm displayed a higher catalytic activity due to the best combination of the Co dispersion and reduction degree. The product distribution strongly depended on the mesoporous diameter due to the following two reasons: 1) the difference in the H2 /CO ratio on the active sites due to the diffusional limitations of CO in the mesopores; 2) the Co crystallite size effect. In addition, large pellet catalysts (800–1700 μm) exhibited similar product distributions to small pellet catalysts (180–250 μm), which indicated that the macropores played an important role in reducing internal diffusion limitations for large pellet catalysts.